Acidic Microenvironment Determines Antibiotic Susceptibility and Biofilm Formation of Pseudomonas aeruginosa - Lin, Qiao; Pilewski, Joseph M.; Di, Y. Peter (Frontiers in Microbiology, 2021)
Pseudomonas aeruginosa is the most prevalent bacterial species that contribute to cystic fibrosis (CF) respiratory failure. The impaired function of cystic fibrosis transmembrane conductance regulator leads to abnormal epithelial Cl- /HCO3- transport and acidification of airway surface liquid. However, it remains unclear why the CF lung is most commonly infected by Pseudomonas aeruginosa versus other pathogens. We carried out studies to investigate if lower pH helps Pseudomonas aeruginosa adapt and thrive in the CF-like acidic lung environment. Our results revealed that Pseudomonas aeruginosa generally forms more biofilm, induces antibiotic resistance faster in acidic conditions, and can be reversed by returning the acidic environment to physiologically neutral conditions. Pseudomonas aeruginosa appears to be highly adaptive to the CF-like acidic pH environment. By studying the effects of an acidic environment on bacterial response, we may provide a new therapeutic option in preventing chronic Pseudomonas aeruginosa infection and colonization.